All reviews are not the same: A systematic review on requesting skills and speech generating devices is undone by serious methodological issues. Issue 2 (2nd April 2016) - Alzrayer, Nouf M.; Banda, Devender R.
Abstract : Still, K., Rehfeldt, R. A., Whelan, R., May, R., & Dymond, S. (2014). Facilitating requesting skills using high-tech augmentative and alternative communication devices with individuals with autism spectrum disorders: A systematic review. Research in Autism Spectrum Disorders, 8, 1184–1199. doi:10.1016/j.rasd.2014.06.003 Source of funding and declaration of interests : This systematic review was funded by a grant from10.13039/100000073 Autism Speaks (#8049). The original authors did not report if there were any conflicts of interest.